ANALISIS CAMPUR KODE PADA MAHASISWA ASAL MAYBRAT DI UNIMUDA SORONG - tubur, jenia alisiah (FRASA: Jurnal Keilmuan, Bahasa, Sastra, dan Pengajarannya, 2023)
The aim of this research is to describe code mixing among Maybrat students at Unimuda Sorong. The research approach used in this research is descriptive qualitative. This research will be conducted at the UNIMUDA Campus, Sorong Regency. The subjects of this research were UNIMUDA students from Maybrat. Observation and documentation data collection techniques. Data analysis techniques use Milles and Hubberman, namely data collection techniques, data reduction, data presentation, and drawing conclusions. Data validity test Data validity tests in qualitative research include testing, credibility (interbar validity), transferability (external validity), dependability (reliability), and confirmability (objectivity). Based on data analysis regarding code mixing among Native Maybrat students, it can be concluded that the code mixing found in the speech incidents of families of Native Maybrat students is divided into two, namely internal code mixing. Code mixing is divided into three types, namely (a) word insertion, (b) phrase insertion, (c) clause insertion